2003
DOI: 10.1380/jsssj.24.417
|View full text |Cite
|
Sign up to set email alerts
|

表面処理炭素材料によるホルムアルデヒド除去

Abstract: Recently, formaldehyde liberated from wallpapers, furnitures and adhesive agents in new buildings and houses cause troubles in human health, and this is called the sick building symdrome. In this study, the carbonaceous materials are prepared from coffee grounds by microwave treatment or by surface-treatments with two different silane coupling agents. We estimated the removal efficiency of formaldehyde by such materials. The water contents of coffee grounds are larger than those of other wastes and thus they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is known that formaldehyde is easily adsorbed by adsorbents possessing a polar surface. In fact, it has been reported that the ability of activated carbon to adsorb formaldehyde increased with an increase in the number of amino groups on the surface of the activated carbon after amination, independent of the specific surface area ( , ). Other studies report that the capability of activated carbon to adsorb harmful gases is dependent on the carbonizing temperature because acidic functional groups, such as carboxyl groups, assisting the activated site to adsorb formaldehyde are removed at appropriate tem peratures ( , ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that formaldehyde is easily adsorbed by adsorbents possessing a polar surface. In fact, it has been reported that the ability of activated carbon to adsorb formaldehyde increased with an increase in the number of amino groups on the surface of the activated carbon after amination, independent of the specific surface area ( , ). Other studies report that the capability of activated carbon to adsorb harmful gases is dependent on the carbonizing temperature because acidic functional groups, such as carboxyl groups, assisting the activated site to adsorb formaldehyde are removed at appropriate tem peratures ( , ).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee grounds are vegetable biomass being burned for disposal, but they will have to be reused in a circulation-type society. We have already reported lead, dyes and formaldehyde removal by coffee grounds based toxic removal technologies (1)(2)(3). In these studies, the activated carbons were prepared from coffee grounds and rice hulls by chemical activation using sodium hydroxide, potassium hydroxide and zinc chloride (4).…”
Section: Introductionmentioning
confidence: 99%